Pemilihan Tipe Produk Unggulan dengan Menggunakan Metode Linear Programming dan Peramalan Permintaan Menggunakan Time Series - Muzakki, Hakam (Universitas Trunojoyo Madura, 2009)
One weaknees in Small and Medi um Enterpri se offurniture, the reasearch didn't calculate some materia l requirements which need ed by SME's intuition and also experiment (trial and error) . The result of the research expected SME' sfurniture improved management sy stem and inventory system in order to compete among of 2.426 SME others 118 industrial fUrniture (Deprindag fa tim, 2003). Some of s tage to improve system and management operation required f easible methorie to evaluated. Optimal solution by LINDO got to pro d uce and sold 120 unit doors, 84 unit table, 33 unit cuboard and chair and hanger produced only order . Forecast methode used decomposi tion better than winter's due to error degree, datas obtained in demmend 2007 up to 2008.Keywords: SME's Furniture, Linier Programming, Time Series